Interprofessional education in the master of clinical pharmacy clinical clerkship - Jamludin, Nurul Ashikin; Ismail, Farhana Fakhira; Dali, Ahmad Fauzi; Ibrahim, Norkasihan; Zakaria, Yuslina (Faculty of Pharmacy, 2026)
Interprofessional education (IPE) has become an essential component in healthcare training, as collaborative practice is fundamental to improving patient outcomes. The World Health Organisation (WHO) in 2010 defined IPE as an approach in which students from different professional backgrounds learn with, from, and about each other to enable effective collaboration and improve health outcomes. The primary goal is to foster a "collaborative practice-ready" workforce that can work effectively and contribute to improving team-based, patient-centered care. The Master of Clinical Pharmacy Clinical Clerkship integrates interprofessional teaching by facilitating postgraduate pharmacy students to engage directly with clinical specialists.